2022
DOI: 10.3390/insects13111032
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of a Petroleum-Derived Spray Oil and an Organosilicone Surfactant on Listronotus maculicollis (Kirby) Adults in Laboratory and Greenhouse Bioassays

Abstract: The annual bluegrass weevil (ABW), Listronotus maculicollis (Kirby), is a severe pest of golf course turf in eastern North America. The development of pyrethroid- and multiple-resistant populations has created a dire need for novel tactics to control adults. We examined the insecticidal properties of a petroleum-derived spray oil (PDSO; Civitas Turf Defense™.) and an organosilicone, nonionic soil surfactant (Silwet L-77®) in laboratory and greenhouse bioassays. Civitas and Silwet killed > 75% of ABW adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bees sited downwind of feedyards became coated with PM, which may have exacerbated toxicity by clogging spiracles and potentially inducing anoxia (see Figure S2). 45 Recent laboratory-based experiments have demonstrated that agrochemical-free PM generated from organic cattle manure is not toxic to pollinators 46 which indicates that agrochemicals bound to fugitive feedyard PM are most likely responsible for the elevated mortality observed among bees sited downwind of feedyards in the present study. Additionally, pesticides that were not included in our analyses, but nevertheless previously documented to occur in fugitive feedyard PM (e.g., piperonyl butoxide, boscalid, pyraclostrobin, etc.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Bees sited downwind of feedyards became coated with PM, which may have exacerbated toxicity by clogging spiracles and potentially inducing anoxia (see Figure S2). 45 Recent laboratory-based experiments have demonstrated that agrochemical-free PM generated from organic cattle manure is not toxic to pollinators 46 which indicates that agrochemicals bound to fugitive feedyard PM are most likely responsible for the elevated mortality observed among bees sited downwind of feedyards in the present study. Additionally, pesticides that were not included in our analyses, but nevertheless previously documented to occur in fugitive feedyard PM (e.g., piperonyl butoxide, boscalid, pyraclostrobin, etc.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the other hand, the high mortality of D. echinocacti with mineral oil, alone, is due to the action Mode of this material, covering the waxy carapace of scale insects with a thin film and killing them by asphyxiation (Martín-López et al 2006). Furthermore, mineral oils are non-polar and therefore more likely to penetrate the hydrophobic integument of the scale mealybug (McGraw et al 2022) as shown for eggs, nymphs, and adults of the mealybugs Lepidosaphes beckii (Newman) and Parlatoria ziziphus (Lucas) (Hemiptera: Diaspididae) on citrus plants treated with mineral oil in Sheben El-Kanater, Caliubia province, Egypt (Helmy et al 2012).…”
Section: Experiments 2: Laboratory Mortalitymentioning
confidence: 99%